2021
DOI: 10.3390/children8080686
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Autonomic Regulation, Adiposity Indexes and Metabolic Profile in Children and Adolescents with Overweight and Obesity

Abstract: Early obesity predicts initial modifications in cardiac and vascular autonomic regulation. The aim of this study was to assess the possible interaction between non-invasive measures of autonomic cardiovascular control and peripheral endothelium regulation in children with overweight and obesity. We involved 114 young subjects (77M/37F, 12.7 ± 2.2 years) with normal weight (NW, n = 46,) to overweight or obesity (OB, n = 68). Multivariate statistical techniques utilizing a collection of modern indices of autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…The study of ANS in a clinical setting may represent an important diagnostic tool, in order to identify early alterations preceding full-blown diseases and/or to highlight improvement following weight reduction interventions. In line with our previous findings revealing a correlation between ANS dysfunction and metabolic alterations [ 52 , 53 , 57 ], in the present study, we observed a progressive improvement of ANS regulation following both smaller and greater weight reduction (after one month-prehabilitation and BS, respectively). To the best of our knowledge, this progressive improvement (LT p < 0.001 for both ANSI and Alpha Index) has been never observed hitherto.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study of ANS in a clinical setting may represent an important diagnostic tool, in order to identify early alterations preceding full-blown diseases and/or to highlight improvement following weight reduction interventions. In line with our previous findings revealing a correlation between ANS dysfunction and metabolic alterations [ 52 , 53 , 57 ], in the present study, we observed a progressive improvement of ANS regulation following both smaller and greater weight reduction (after one month-prehabilitation and BS, respectively). To the best of our knowledge, this progressive improvement (LT p < 0.001 for both ANSI and Alpha Index) has been never observed hitherto.…”
Section: Discussionsupporting
confidence: 93%
“…Recent data also show a role of obesity in worsening COVID-19 prognosis [ 51 ]. Overweight and obesity are characterized by an impairment of ANS prior to the onset of diabetes or cardiac disease [ 3 , 5 , 6 , 52 , 53 ], thus suggesting a possible role of ANS alongside other etiopathogenetic mechanisms in the development of these conditions. Of particular interest is the relationship between insulin resistance and ANS control in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…In all the participants, height, weight, puberal stage, BMI, BMI z-score, waist circumference (WC), and waist-to-height ratio (WHtR) were measured as previously described [ 29 ]. Briefly, weight was measured using a scale platform (Seca, Hamburg, Germany) with children not wearing shoes and in light clothing, standing upright, hands at their sides, and looking straight ahead.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, weight was measured using a scale platform (Seca, Hamburg, Germany) with children not wearing shoes and in light clothing, standing upright, hands at their sides, and looking straight ahead. Height was measured using a Harpenden stadiometer (Holtain Ltd., Cross-well, UK) [ 29 ]. BMI was calculated as body weight (kilograms) divided by height (meters squared) and converted into BMI z scores using WHO reference values [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Childhood obesity has been linked to the early onset of various chronic conditions, such as type 2 diabetes and systemic arterial hypertension [ 3 ]. Additionally, research demonstrates that obesity is often attended by earlier dysfunction of the autonomic nervous system [ 4 ]. Adverse obesity-related health consequences have been associated with possible cognitive decline and increased body mass index, while central adiposity has been shown to be correlated with performance impairments under task conditions that require executive control [ 5 ].…”
Section: Introductionmentioning
confidence: 99%